Analisis sifat listrik nanokomposit NiFe2O4/PANi yang disintesis dengan metode sol gel (Analysis of the electrical properties of NiFe2O4 / PANi nanocomposites synthesized by sol gel method) - Sri Rahma Yani; Djusmaini Djamas (PILLAR OF PHYSICS, 2019)
NiFe2O4/PANi nanocomposite was synthesized using the sol gel method with satisfying 2.5%, 5%, 30%, 50%, and 70% NiFe2O4 to PANi. Characterization of particle size, sample thickness, conductivity, and capacitance using X-ray diffraction (XRD), Scanning Microscope Electrons (SEM), and LCR Meter. Information sizes in 2.5%, 5%, 30%, 50%, and 70% are 37.16 nm, 54.16 nm, 31.2 nm, 42.23 nm, and 39.16 nm respectively. The electrical properties of NiFe2O4 / PANi Nanocomposites are used by using LCR meters, namely resistance and capacitance. The values of electrical conductivity generated from various meetings were 2.5%, 5%, 30%, 50%, and 70%, respectively 0.13 S / m, 0.08 S / m, 0.16 S / m, 0.57 S / m, and 0.25 S / m. From the measurement results show that the values of electrical conductivity in NiFe2O4 / PANi 2.5% high compared to NiFe2O4 / PANi 5% and again increase along with the increasing composition of NiFe2O4. However, in the condition of NiFe2O4 / PANi nanocomposite 70% electrical conductivity decreased. For large amounts of NiFe2O4 to PANi, the electrical conductivity increases. NiFe2O4 / PANi capacitance through a difference of 2.5%, 5%, 30%, 50%, and 70% resulted from successive measurements of 193.32 nF, 83.77 nF, 0.001 nF, 0.55 nF, 0 , 44 nF. The capacitance of NiFe2O4 / PANi shows that the greater the amount of NiFe2O4 to PANi the capacitance decreases.